An Indicator of Future Inflation Extracted from the Steepness of the Interest Rate Yield Curve Along Its Entire Length - Frankel, J. A.; Lown, C. S. (Quarterly Journal of Economics, 1994)
The term-structure slope contains information about expected future inflation. Mishkin shows that the spread between the twelve-month and three-month interest rates helps predict the difference between twelve-month and three-month inflation. We apply a simple existing framework, which lets the real interest rate vary in the short run but converge to a constant in the long run, to this problem. The appropriate indicator of expected inflation uses the entire length of the yield curve, estimating the steepness of a specific nonlinear transformation, rather than being restricted to a spread between two points. The resulting indicator better predicts inflation, over 1960–1991.